2016
DOI: 10.1016/j.elecom.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial determination of diffusible hydrogen concentrations proximate to pits in a Fe–Cr–Ni–Mo steel using the Scanning Kelvin Probe

Abstract: The diffusible hydrogen concentration (C H,diff) was mapped spatially, proximate to acidic corrosion pits formed in MgCl 2 droplets, on an ultra-high strength stainless steel using a Scanning Kelvin Probe (SKP). A secondary hardened martensitic stainless steel (Fe-11Ni-12Cr-1Mo-0.005C-0.02Mn wt%) was evaluated. Predetermined, uniform C H,diff levels quantified by electrochemical extraction after homogeneous cathodic charging, were calibrated versus the SKP potential at 57 %RH (0.16 kPa H 2 O, 20.26 kPa O 2 , 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
(40 reference statements)
1
20
0
1
Order By: Relevance
“…For hydrogen visualization, most of the recent technological efforts have been focused on three specific topics: quantification of the local hydrogen content [5][6][7], multi-scale hydrogen distribution observations [8,9], and kinetically resolved hydrogen mapping [10][11][12]. In recent studies [12][13][14], scanning Kelvin probe force microscopy (SKPFM) has been reported to enable sequential kinetic analysis of microstructural hydrogen diffusion/segregation.…”
mentioning
confidence: 99%
“…For hydrogen visualization, most of the recent technological efforts have been focused on three specific topics: quantification of the local hydrogen content [5][6][7], multi-scale hydrogen distribution observations [8,9], and kinetically resolved hydrogen mapping [10][11][12]. In recent studies [12][13][14], scanning Kelvin probe force microscopy (SKPFM) has been reported to enable sequential kinetic analysis of microstructural hydrogen diffusion/segregation.…”
mentioning
confidence: 99%
“…The scanning Kelvin probe (SKP) [2][3][4] and scanning Kelvin probe force microscopy (SKPFM) [5,6] have been used to detect hydrogen in a range of materials and alloys. Scanning electrochemical microscopy (SECM) has recently been reported as a new technique to detect hydrogen in steel [7].…”
Section: Introductionmentioning
confidence: 99%
“…At 20 o C and H 2 S partial pressure (p H2S ) of 0.83 kPa, it was reported that fatigue crack growth was controlled by hydrogen diffusion at pH = 7, whereas some characteristics of stress corrosion cracking were observed at pH = 12 [21][22][23]. A spatial mapping study using a Scanning Kelvin Probe at the sub-mm scales by Schaller and Scully found a close correlation between pit formation and high hydrogen production in acidic corrosion [24]. Electrochemical corrosion reactions have a significant impact on the initiation and propagation of pits and cracking.…”
Section: Introductionmentioning
confidence: 99%